Role of Neurofilament Light Chain as a Potential Biomarker for Alzheimer's Disease: A Correlative Meta-Analysis - Jin, Mei; Cao, Li; Dai, Yan-ping (Frontiers in Aging Neuroscience, 2019)
Neurofilament light (NFL) is a putative biomarker of neurodegeneration. This study evaluates the correlative association of NFL with Alzheimer’s disease (AD) indices. Relevant studies were identified after a literature search in electronic databases and study selection was based on pre-determined eligibility criteria. Correlation coefficients between NFL levels and important AD indices reported by individual studies were pooled as z-scores. Meta-regression analyses were performed to evaluate the relationships between important covariates. Data from 38 studies (age 68.3 years [95% confidence interval (CI): 65.7, 70.9]; 54 % [95%CI: 50, 57] females) were used. Meta-analyses of correlation coefficients reported by the included studies showed that NFL levels in blood and cerebrospinal fluid (CSF) correlated well (r=0.59 [95%CI: 0.45, 0.71]; p˂0.0001). NFL levels correlated with MMSE score (r=−0.345 [95%CI: −0.43, −0.25]; p=0.0001), and age (r=0.485 [95% CI: 0.35, 0.61]; p=0.00001). CSF NFL levels correlated with total tau (t-tau; r=0.39 [95%CI: 0.27, 0.50]; p=0.0001), phosphorylated tau (p-tau; r=0.34 [95%CI: 0.19, 0.47]; p=0.00001), and neurogranin (r=0.25 [95%CI: 0.12, 0.37]; p=0.001) but not with beta amyloid (Aβ) (r=0.00 [95%CI: −0.13, 0.12]; p=0.937). In meta-regression, MMSE scores were associated inversely with blood NFL (metaregression coefficient (MC) −0.236 [95% CI:−0.40, −0.072; p=0.008), and age (MC −0.235 [−0.36, −0.11]; p=0.001) and positively with CSF Aβ-42 (MC 0.017 [0.010, 0.023]; p=0.00001). NFL has good correlations with t-tau, and p-tau in CSF and CSF NFL levels correlates well with blood NFL levels. These results show that NFL can be a useful biomarker for improving diagnosis and predicting prognosis in AD patients especially if age weighted.